2016
DOI: 10.1002/mame.201500340
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Porous Polymer Coatings on Complex Substrates Using Vapor Phase Precursors

Abstract: In this work, porous poly(methacrylic acid) (PMAA) coatings are formed on complex substrates using vapor phase precursors. The porous coatings are created by partially polymerizing solid monomer deposited onto the substrate. The conformality of the porous PMAA coatings is studied on the external and internal surfaces of cylindrical substrates. Flow effects lead to thickness variations in the θ‐direction while thermal gradients and monomer depletion effects lead to thickness variations in the z‐direction. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Novel iCVD processes allowed formation of free-standing microporous poly(MAA) layers of interest for membrane separation and tissue engineering applications. 64,76,77 For paper-based microfluidics, the low surface growth temperature of iCVD allowed MAA-based membranes to be fabricated directly on paper substrates. 78 Annealing these membranes resulting in condensation of some of the -COOH groups to anhydride functionalities, producing a finer pore structure.…”
Section: Ph-responsive Icvd Hydrogelsmentioning
confidence: 99%
“…Novel iCVD processes allowed formation of free-standing microporous poly(MAA) layers of interest for membrane separation and tissue engineering applications. 64,76,77 For paper-based microfluidics, the low surface growth temperature of iCVD allowed MAA-based membranes to be fabricated directly on paper substrates. 78 Annealing these membranes resulting in condensation of some of the -COOH groups to anhydride functionalities, producing a finer pore structure.…”
Section: Ph-responsive Icvd Hydrogelsmentioning
confidence: 99%
“…Free radicals that are formed by thermally cleaving the initiator molecules react with the monomer to start polymerization. Unreacted solid monomer is then removed through sublimation, and the porous polymer membrane remains. ,, Larger pores on the order of tens to hundreds of micrometers in magnitude form due to empty spaces between the solid microstructures and smaller pores form on the order of hundreds of nanometers inside the microstructures. Using this method, we have previously shown the fabrication of porous-on-porous membranes, asymmetric membranes, and patterned porous polymer membranes …”
Section: Introductionmentioning
confidence: 99%
“…Our group recently demonstrated that the iCVD process can also be used to fabricate membranes by increasing the monomer partial pressure above its saturation pressure and lowering the substrate temperature below the freezing point of the monomer. These nonconventional conditions lead to the simultaneous deposition of solid monomer and polymerization . The unreacted solid monomer is removed after the deposition which leads to the formation of membranes with dual‐scale porosity.…”
Section: Introductionmentioning
confidence: 99%
“…These nonconventional conditions lead to the simultaneous deposition of solid monomer and polymerization. [ 25,26 ] The unreacted solid monomer is removed after the deposition which leads to the formation of membranes with dual-scale porosity.…”
Section: Introductionmentioning
confidence: 99%